Nouvelles récentes de l'article 96 - Duplé, Nicole (Les Cahiers de droit, 1977)
When called upon, to ascertain the ambit of the application of section 96 of the B.N.A. Act (1867), our courts have devised a method of reasoning by historical analogy between different types of jurisdictions. In Tomko v. Labour Relations Board (N.S.) and al., the Supreme Court was given the opportunity to make a clear synthesis of the principles underlying such an approach. Although the Court's decision makes no innovations in this respect, it establishes clear guidelines to be followed by the judiciary when it shall next be called upon to pronounce itself on the constitutionnality of the conferral of jurisdiction upon inferior tribunals or provincial administrative organisms in the light of section 96. The Supreme Court is now hearing the appeal in P.g. du Québec et Tribunal des Transports v. Farrah. In that case, the Court of Appeal held that when the Transport Tribunal hears an appeal from the Transport Commission on questions of law only, it exercises a jurisdiction which is analogous to the superintending power of the Superior Court. The Court of appeal therefore considered that the judges of the Transport Tribunal fall under the application of section 96. If the Supreme Court were to confirm the appeal tribunal's decisions it most probably would also have to examin the constitutionnality of certain "privative" clauses; if it were to refuse to adopt the Court of appeal's view, it would render possible the establishment of an administrative appeal court whose judges would be nominated by the Province.